Blockchain Competition Between Miners: A Game Theoretic Perspective - Altman, Eitan; Menasché, Daniel; Reiffers-Masson, Alexandre; Datar, Mandar; Dhamal, Swapnil; Touati, Corinne; El-Azouzi, Rachid (Frontiers in Blockchain, 2020)
We model the competition over mining resources and over several cryptocurrencies as a non-cooperative game. Leveraging results about congestion games, we establish conditions for the existence of pure Nash equilibria and provide efficient algorithms for finding such equilibria. We account for multiple system models, varying according to the way that mining resources are allocated and shared and according to the granularity at which mining puzzle complexity is adjusted. When constraints on resources are included, the resulting game is a constrained resource allocation game for which we characterize a normalized Nash equilibrium. Under the proposed models, we provide structural properties of the corresponding types of equilibrium, e.g., establishing conditions under which at most two mining infrastructures will be active or under which no miners will have incentives to mine a given cryptocurrency.